2019
DOI: 10.1542/peds.2018-3036
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of Cerebral Aneurysms in Children

Abstract: BACKGROUND: Our aim was to report the long-term clinical and imaging outcomes of ≤15-year-old children treated for ruptured or symptomatic cerebral aneurysms and to identify prognostic factors for clinical outcome, recurrence, and rebleeding. METHODS: We retrospectively identified all pediatric cases of cerebral aneurysm from 2000 to 2015 and then prospectively evaluated long-term occlusion using brain MRI and clinical outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 26 publications
(32 reference statements)
1
37
1
Order By: Relevance
“…High-potential leptomeningeal circulation also plays an important role in decreasing the effect of vasospasm (15). Aneurysm rebleeding after SAH appears in 52-60% cases, and reports regarding its outcomes have conflicted among studies (3,20). While one study identified aneurysm rebleeding as the primary cause of mortality (76% of total deaths), another case series reported that approximatively 80% of rebleeding cases were associated with good postoperative outcomes (3,17).…”
Section: █ Materials and Methodsmentioning
confidence: 99%
“…High-potential leptomeningeal circulation also plays an important role in decreasing the effect of vasospasm (15). Aneurysm rebleeding after SAH appears in 52-60% cases, and reports regarding its outcomes have conflicted among studies (3,20). While one study identified aneurysm rebleeding as the primary cause of mortality (76% of total deaths), another case series reported that approximatively 80% of rebleeding cases were associated with good postoperative outcomes (3,17).…”
Section: █ Materials and Methodsmentioning
confidence: 99%
“…17 Prognosis and follow-up Some authors showed that, despite a death rate of about 20%, two-thirds of children younger than 15 years who suffered from ruptured or symptomatic cerebral aneurysms had long-term favourable outcomes. 20 Cerebral ischaemia occurring initially or delayed within the first few months was a factor of poor clinical outcome, and an aneurysm larger than 5mm was the only factor associated with recurrence. 20 The longer anticipated lifespan and greater recurrence risk of paediatric intracranial aneurysms explain why these patients need an aggressive therapeutic approach with cure as the goal and a lifelong imaging follow-up to detect aneurysm recurrence and de novo aneurysm formation.…”
Section: Clinical Aspectsmentioning
confidence: 99%
“…20 Cerebral ischaemia occurring initially or delayed within the first few months was a factor of poor clinical outcome, and an aneurysm larger than 5mm was the only factor associated with recurrence. 20 The longer anticipated lifespan and greater recurrence risk of paediatric intracranial aneurysms explain why these patients need an aggressive therapeutic approach with cure as the goal and a lifelong imaging follow-up to detect aneurysm recurrence and de novo aneurysm formation. 19,20 As in the adult population, for patients with unruptured aneurysms there were no clear clinical data to propose a conservative attitude or any other treatment.…”
Section: Clinical Aspectsmentioning
confidence: 99%
See 2 more Smart Citations